Ekho nedeli . Ekho nedeli . Echoes of the Week . Эхо недели - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Interview with Oleg Soskovets about economic reforms in Russia; a cease-fire agreement in the Georgian-Abkhaz conflict; an analysis of the economic consequences of armed conflicts in former Soviet territories; the Soviet Union's collapse; enterprise bankruptcy. Featured in the program: Soskovets, Oleg (First Deputy Prime Minister of the Russian Federation); Liubchenko, Nikolai (General Consul of the Embassy of Ukraine) Интервью с Олегом Сосковцом об экономических реформах в Российской Федерации; договоренность у прекращении огня в грузино-абхазском конфликте; анализ экономических последствий вооруженных конфликтов на территории бывшего СССР распада СССР; о банкротстве предприятий. В программе участвуют: Сосковец, Олег (Первый заместитель председателя Правительства Российской Федерации); Любченко, Николай (Генеральный консул посольства Украины)